High‐resolution (40 m) simulation of a severe case of low‐level windshear at the Hong Kong International Airport—Comparison with observations and skills in windshear alerting. (4th August 2021) - Chan, P. W.; Lai, K. K.; Li, Q. S.
Abstract: A case of severe low‐level windshear at the Hong Kong International Airport was investigated in this study using large eddy simulation (LES) with a spatial resolution of 40 m. The computer simulation results were compared with the actual observations at the airport, including Doppler light detection and ranging (LIDAR) systems and surface automatic weather stations. The LES was found to be capable of reproducing the tiny vortices associated with the terrain‐disrupted airflow. Some interesting features of surface temperature and vertical velocity were also observed in the computer simulation. The simulated and observed meteorological parameters had satisfactory comparison results, although the micro‐scale variability of such parameters still could not be captured by the high‐resolution LES. Finally, the computer‐simulated headwind profiles appeared to have skills in capturing the low‐level windshear reports from the pilots. The headwind refers to the component of the wind along the direction of the flight path to be encountered by the arrival/departing aircraft. The study was novel in the use of the rather large domain for LES simulation and in the application to low‐level windshear alerting. Abstract : Model domain (a): grid 1 (green), grid 2 (blue), grid 3 (red), grid 4 (yellow) and grid 5 (orange). (b) Shows details of grid 5 and the locations of the weather stations discussed in the paper. The extensions to the west and east of each runway are the windshear alerting regions, with tick marks given at 1 nautical mile, 2 nautical miles and 3 nautical miles from the runway end. Height contours are in 100 m. (c) Shows the tephigrams before the event. The sounding is launched at King's Park of Hong Kong.